2008
DOI: 10.1111/j.1399-302x.2008.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Candida albicans and Candida glabrata populations associated with the pathogenesis of denture stomatitis

Abstract: This study has demonstrated that mixed C. albicans and C. glabrata biofilms may play an important role in the pathogenesis associated with severe inflammation in denture wearers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
190
1
36

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(251 citation statements)
references
References 41 publications
14
190
1
36
Order By: Relevance
“…In such studies, C. albicans is reported as being the most prevalent Candida species on the dentures of stomatitis patients, with an incidence of 54-75%, and a lower incidence evident on the dentures on non DS patients (39%) [28][29][30]. In the present study, similar findings were reported, with a 57% incidence of oral colonisation by C. albicans in DS patients and a 22% incidence in non-DS patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In such studies, C. albicans is reported as being the most prevalent Candida species on the dentures of stomatitis patients, with an incidence of 54-75%, and a lower incidence evident on the dentures on non DS patients (39%) [28][29][30]. In the present study, similar findings were reported, with a 57% incidence of oral colonisation by C. albicans in DS patients and a 22% incidence in non-DS patients.…”
Section: Discussionsupporting
confidence: 80%
“…A number of previous investigations have examined the microbiology of DS, particularly with respect to the Candida species colonisation of the oral cavity [28][29][30]. In such studies, C. albicans is reported as being the most prevalent Candida species on the dentures of stomatitis patients, with an incidence of 54-75%, and a lower incidence evident on the dentures on non DS patients (39%) [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Although Lactobacillus species are the most commonly isolated bacteria from DS biofilms, other Candida species, namely C. glabrata, have also been detected [92]. Coinfection with C. glabrata results in upregulation of key virulence genes (ALS3 and HWP1) in C. albicans [93].…”
Section: Denture Stomatitis: Mixing In a Rough Neighbourhoodmentioning
confidence: 99%
“…Patients were excluded from this study if they had been receiving antimicrobial treatment or using prescription mouthwashes within six months prior to sampling. Dentures were removed from the patient's mouth and placed in sterile bags (Fisher Scientific) filled with 50 ml phosphate buffered saline ([PBS, Sigma-Aldrich), and placed in a sonic bath (Ultrawave) for 5 min to remove the biofilm from the surface (24). The denture sonicate was centrifuged for 10 min at 3700 x g [6000 r.p.m.…”
Section: Patient Samplingmentioning
confidence: 99%